Divulgação científica no Museu Amazônico: uma oportunidade de democratização da ciência - Vasconcellos, Regina Lucia de Souza (2016)
This study aimed to analyze to what extent the Amazon Museum contributes to the dissemination Science in Primary School. The study was conducted with own professionals museum and at schools located around the institution. The methodological perspective was a case study, based on qualitative research, using the following instruments: bibliographic research, documentary and semi-open interviews to collect data, which subsequently analyzed served to compose the results and the final considerations. This study showed the following: from the mission to preserve and value the historic and cultural heritage of the Amazon: the Amazon Museum of the Federal University of Amazonas. Which disseminate the scientific knowledge especially in the areas of History, Archaeology and Anthropology by means of presentations exhibitions and educational activities that enable knowledge of the Amazon region and the traditional societies that inhabit it; and the directors, pedagogues, teachers and students interviewed recognize the Museum as a space for the dissemination of Science Knowledge